A proposal to estimate the valuation of small and medium size companies using geographically comparable information; Propuesta para estimar la valoracioń de pequen\~as y medianas empresas mediante el uso de informacioń geograf́icamente comparable - Mariluz Mate; Paolo Occhino (Small Business International Review (SBIR), 2020)
A common prerequisite in valuation analysis is the availability of temporal information on financial variables. Nevertheless, reduced size companies-representing more than 98% on current productive systems- fail to have available temporal information to estimate valuations. In this paper, we offer a procedure for estimating reduced size companies' values under the hypothesis that spatial behaviour matters for valuations. With this aim, we present the theoretical background for this hypothesis and introduce a spatial proposal with a case study of industrial companies where the significant role of space on firms' valuations is previously tested. This analysis shows the relevance of spatial information in firms' valuation confirming the predictive capability of our approach applying the out of sample methodology. – – Un requisito previo en cualquier anaĺisis de valoracioń es la disponibilidad de informacioń temporal para determinada variables financieras. Las pequen\~as y medianas empresas, aunque representan maś del 98% en los sistemas productivos actuales, no disponen de informacioń temporal para estimar las valoraciones. En este documento, ofrecemos un procedimiento para estimar los valores de las empresas de taman\~o reducido bajo la hipot́esis de que el comportamiento espacial afecta a las valoraciones. Con este objetivo, presentamos los antecedentes teoŕicos para esta hipot́esis e introducimos una propuesta espacial con un estudio de caso de empresas industriales, donde el papel significativo del espacio en las valoraciones de las empresas se ha probado previamente. Este anaĺisis muestra la relevancia de la informacioń espacial en la valoracioń de las empresas confirmando la capacidad predictiva de nuestro enfoque aplicando la metodologiá fuera de muestra.
Keywords: G12; R12; R51; 650; location; company valuation; geographically comparable companies; discounting cash flows model; SMEs; localizacioń; valoracioń de empresas; empresas geograf́icamente comparables; modelo de descuento de flujos de efectivo; PYMEs